Common bean reaction to angular leaf spot comprises transcriptional modulation of genes in the ALS10.1 QTL - Oblessuc, Paula R.; Matiolli, Cleverson C.; Chiorato, Alisson F.; Camargo, Luis E. A.; Benchimol-Reis, Luciana L.; Melotto, Maeli (Frontiers in Plant Science, 2015)
Genetic resistance of common bean (Phaseolus vulgaris L.) against angular leaf spot (ALS), caused by the fungus Pseudocercospora griseola, is conferred by quantitative trait loci (QTL). In this study, we determined the gene content of the major QTL ALS10.1 located at the end of chromosome Pv10, and identified those that are responsive to ALS infection in resistant (CAL 143) and susceptible (IAC-UNA) genotypes. Based on the current version of the common bean reference genome, the ALS10.1 core region contains 323 genes. Gene Ontology (GO) analysis of these coding sequences revealed the presence of genes involved in signal perception and transduction, programmed cell death (PCD), and defense responses. Two putative R gene clusters were found at ALS10.1 containing evolutionary related coding sequences. Among them, the Phvul.010G025700 was consistently up-regulated in the infected IAC-UNA suggesting its contribution to plant susceptibility to the fungus. We identified six other genes that were regulated during common bean response to P. griseola; three of them might be negative regulators of immunity as they showed opposite expression patterns during resistant and susceptible reactions at the initial phase of fungal infection. Taken together, these findings suggest that common bean reaction to P. griseola involves transcriptional modulation of defense genes in the ALS10.1 locus, contributing to resistance or susceptibility depending on the plant-pathogen interaction.